2023
DOI: 10.1186/s43556-023-00145-z
|View full text |Cite|
|
Sign up to set email alerts
|

Activation and induction of antigen-specific T follicular helper cells play a critical role in recombinant SARS-CoV-2 RBD vaccine-induced humoral responses

Songhao Yang,
Liangwei Duan,
Chan Wang
et al.

Abstract: The role of follicular T helper (Tfh) cells in humoral response has been considered essential in recent years. Understanding how Tfh cells control complex humoral immunity is critical to developing strategies to improve the efficacy of vaccines against SARS-CoV-2 and other emerging pathogens. However, the immunologic mechanism of Tfh cells in SARS-CoV-2 receptor binding domain (RBD) vaccine strategy is limited. In this study, we expressed and purified recombinant SARS-CoV-2 RBD protein in Drosophila S2 cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported that a funding number needed to be added in the funding section.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that a funding number needed to be added in the funding section.…”
mentioning
confidence: 99%